O Exame Nacional do Ensino Médio: um estudo sobre seus usos (1998 2012) - Carnaval, Marilya Mariany (2014)
Since our perspective was to understand the development of the Enem, which, according to its developers, has the objective of introducing changes and improvements in Secondary Level (Ensino Médio), during this research we: a) identified changes in Enem test; b) verified the performance of the public school student; c) identified the purposes introduced to the exam from 1998 to 2012. Our objects of analysis were: the tests, the anual reports, the theoretical and methodological texts, 1999 Enem's final report. As theoretical reference we adopted the perspective of the studies developed by the thinkers of the Critical Theory of Society, among them, Herbert Marcuse and his concepts of the technological rationality and the principle of performance, and Theodor W. Adorno and the concept of formation. To collect the grades, we used the micro data of Enem and to analyse the statistics of the data we used the program Statistics Program of Social Science, version 21.0 (SPSS 21.0). Through the analysis we identified two models of exam, one before and the other after 2009. The changes in the exam in 2009 is a wide group of structural modification in the objective part of the exam and also in the essay: the questions' format, the array of reference, the operationalization of the exam, and the methodology to calculate the results. The interpretation of the grades indicates that the new Enem (2009 to 2012) presents better results in comparison to the original Enem (2001 to 2008). As a conclusion, it is possible to observe an overvaluation of Enem as an instrument:the methodology, the number of questions and the content are changed, several new purposes are introduced in a single exam, but the student's learning is not discussed